Current development status of key technologies for high-performance on-board interconnection buses — analysis of TSN bus application prospects in aerospace - Zhao, Wenjie; Zhang, Wanying; Rao, Jianing; Han, Shuangxue; Jia, Wenyuan; Song, Jingxing; Ma, Miao; Dong, Zhenxing; Yin, Guodong; Zhu, Yan; An, Junshe (Frontiers in Astronomy and Space Sciences, 2025)
This paper conducts a comprehensive survey and analysis of interconnection buses for space applications both domestically and internationally in recent years. In response to the future demands of satellites for high-performance computing, high-efficiency data processing, and high-speed data transmission in space missions, it proposes the integration of TSN (Time-Sensitive Networking) and RDMA (Remote Direct Memory Access) as a novel bus architecture for aerospace systems. The study investigates the developmental trajectory, practical implementations, and future prospects of TSN technology, alongside a parallel examination of RDMA’s evolution, deployments, and emerging trends. Synthesizing these findings, the paper presents a forward-looking perspective on space applications leveraging the TSN+RDMA high-performance interconnection bus.